The conjugation of phenols with phosphate in grass grubs and flies - Binning, Anna (1967)
1. Houseflies, blowflies and New Zealand grass grubs were dosed with 1-naphthol, 2-naphthol or p-nitrophenol. 2. The corresponding monoaryl phosphates were identified in extracts of insects or excreta along with the β-glucosides and ethereal sulphates of the phenols. 3. No diaryl phosphates or glucosiduronates were detected but an unidentified metabolite of [(14)C]1-naphthol was present in extracts of flies dosed with [(14)C]1-naphthol.